The stoichiometric dissociation constants of carbonic acid in seawater brines from 298 to 267 K. (1st January 2018) - Papadimitriou, Stathys; Loucaides, Socratis; Rérolle, Victoire M.C.; Kennedy, Paul; Achterberg, Eric P.; Dickson, Andrew G.; Mowlem, Matthew; Kennedy, Hilary
Abstract: The stoichiometric dissociation constants of carbonic acid ( K 1 C ∗ and K 2 C ∗ ) were determined by measurement of all four measurable parameters of the carbonate system (total alkalinity, total dissolved inorganic carbon, pH on the total proton scale, and CO2 fugacity) in natural seawater and seawater-derived brines, with a major ion composition equivalent to that of Reference Seawater, to practical salinity (SP ) 100 and from 25 °C to the freezing point of these solutions and −6 °C temperature minimum. These values, reported in the total proton scale, provide the first such determinations at below-zero temperatures and for SP > 50. The temperature (T, in Kelvin) and SP dependence of the current pK 1 C ∗ and pK 2 C ∗ (as negative common logarithms) within the salinity and temperature ranges of this study (33 ≤ SP ≤ 100, −6 °C ≤ t ≤ 25 °C) is described by the following best-fit equations: pK 1 C ∗ = −176.48 + 6.14528 S P 0.5 − 0.127714 SP + 7.396 × 10 −5 S P 2 + (9914.37 − 622.886 S P 0.5 + 29.714 SP ) T −1 + (26.05129 − 0.666812 S P 0.5 ) lnT ( σ = 0.011, n = 62), and pK 2 C ∗ = −323.52692 + 27.557655 S P 0.5 + 0.154922 SP − 2.48396 × 10 −4 S P 2 + (14763.287 − 1014.819 S P 0.5 − 14.35223 SP ) T −1 + (50.385807 − 4.4630415 S P 0.5 ) lnT ( σ = 0.020, n = 62). These functions are suitable for application to investigations of the carbonate system of internal sea ice brines with a conservative major ion composition relative to that of Reference Seawater and within the temperature and salinity ranges of this study.